Addressing the association between driving with an expired vehicle inspection certificate and injury severity after a crash. (29th March 2022) - Martín-delosReyes, Luis Miguel; Martínez-Ruiz, Virginia; Rivera-Izquierdo, Mario; Jiménez-Mejías, Eladio; Pulido-Manzanero, José; Lardelli-Claret, Pablo
Abstract: Objectives: The aim of this study was to quantify the association between driving a vehicle with an expired vehicle inspection certificate (DEVIC) and the severity of injuries sustained by drivers involved in collisions. Methods: A cohort study was designed to compare the incidence of minor injuries, major injuries, and deaths between DEVIC and non-DEVIC drivers involved in collisions. We selected all 51, 305 non-responsible drivers (i.e., drivers who did not commit an error or infraction) involved in clean collisions (those in which only one driver in multivehicle collisions committed a traffic infraction or error) from the population of drivers of four-wheeled motor vehicles involved in crashes recorded in the National Register for Road Traffic Accident Victims in Spain from 2014 to 2017. Results: DEVIC was not related with a greater severity of drivers' injuries. The adjusted estimates for the association between DEVIC and major injuries or death yielded an odds ratio of 0.91 (0.66–1.25), compared to no injuries or minor injuries, and a relative risk ratio of 0.90 (0.65–1.24) compared to no injuries. Conclusions: Although we have not found an association between DEVIC and drivers' injury severity, the study limitations does not allow us to discard the usefulness of periodic vehicle inspection in reducing the risk of more severe injury among drivers involved in road crashes.